Effect of Intracavitary ECG and P-wave Ratio on Neonatal PICC Localization - Lu, Huaxiang; Ling, Yudan; Huang, Liufeng; Liang, Fengdan; Li, Wei; Lu, Xiaomei (Journal of Contemporary Medical Practice, 2025)
Objective: To investigate the relationship between the P-wave size of neonatal PICC intracavitary electrocardiogram (ECG)tip and the position of PICC catheter tipin superior vena cava and its clinical effect. Methods: A total of 184 patients with PIC-C catheterization were enrolled in the study. They were randomly divided into observation group and control group according to the random number table method, 92 cases in each group. The control group took the regular body surface and the chest X-ray positioning after operation, while the observation group was located by intracavitary EC-G P-wave ratio and chest X-ray. The disposable catheter success rate and time of catheterization were compared between the two groups, and the position of catheter tip corresponding to different Pwaves was analyzed. Results: The PICC disposable catheter success rate of the newborns in the observation group was 95. 65(88/92), which was significantly higher than that of the control group (81.52%, 75/92) (P<0.01). The catheterization time and the puncture sitebleeding volume in the observation group were significantly lower than the control group(P<0.01). In the observation group, the tip of the catheter of 1/2 -2/3 R wave was mainly recommended by the guideline, the 1/3-1/2 R wave was mainly 2/3 of the superior vena cava, and the 1/2 2/3 R wave was mainly recommended by the guideline or right atrium, the difference was statistically significant (P<0.05). Conclusions: The P-wave ratio of intracavitary ECG is helpful to locate the tip of neonatal PICC.